2002
DOI: 10.1002/jnr.10154
|View full text |Cite
|
Sign up to set email alerts
|

Visual responses of neurons in the nucleus of the basal optic root to stationary stimuli in pigeons

Abstract: The nucleus of the basal optic root of the accessory optic system in pigeons is involved in generating optokinetic nystagmus, which stabilizes object images on the retina by compensatory eye movements. Previous studies have indicated that basal optic neurons are selective for the direction and velocity of motion. The present study shows that these optokinetic cells also respond to stationary stimuli and thereby could be categorized into three groups. The first group of cells (69.1%) responds to stationary grat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, the transient/sustained ratios at the onset of motion in the preferred direction were larger in the accelerationsensitive neurons, and the value of the transient/sustained ratio was related to the amount of acceleration responsiveness, indicating that part of the transient is related to the presence of response to stimulus acceleration. Previous studies have shown that many directional cells produce transient responses to the onset of motion (Ibbotson et al, 1998;Lisberger and Movshon, 1999;Wylie and Crowder, 2000;Priebe and Lisberger, 2002) and to the appearance of a stationary pattern (Müller et al, 2001;Gu et al, 2002). The onset transients in these cases could convey information about stimulus motion or edge detection (Awatramani and Slaughter, 2000) and may originate from the retinal bipolar cells and/or some synaptic mechanisms (Awatramani and Slaughter, 2000;Müller et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the transient/sustained ratios at the onset of motion in the preferred direction were larger in the accelerationsensitive neurons, and the value of the transient/sustained ratio was related to the amount of acceleration responsiveness, indicating that part of the transient is related to the presence of response to stimulus acceleration. Previous studies have shown that many directional cells produce transient responses to the onset of motion (Ibbotson et al, 1998;Lisberger and Movshon, 1999;Wylie and Crowder, 2000;Priebe and Lisberger, 2002) and to the appearance of a stationary pattern (Müller et al, 2001;Gu et al, 2002). The onset transients in these cases could convey information about stimulus motion or edge detection (Awatramani and Slaughter, 2000) and may originate from the retinal bipolar cells and/or some synaptic mechanisms (Awatramani and Slaughter, 2000;Müller et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The right eye was held open and the left eye was covered. During single-unit recordings in the anaesthetized pigeons, the eye movements were intermittently monitored by the experimenter and no observable eye movements were found (Gu et al 2002). A screen of 130 deg × 140 deg was placed tangential to and 40 cm away from the viewing eye.…”
Section: Methodsmentioning
confidence: 99%
“…found that the nBOR-LM projection is inhibitory, as electrical stimulation of nBOR resulted in a decrease in the activity of LM neurons. By recording from LM after pharmacological inactivation of nBOR, both Gu et al~2002! andCrowder et al~2003b!…”
Section: Functions Of the Small Nbor Neuronsmentioning
confidence: 99%